2015
DOI: 10.1002/2015ja021699
|View full text |Cite
|
Sign up to set email alerts
|

An extensive survey of dayside diffuse aurora based on optical observations at Yellow River Station

Abstract: By using 7 years optical auroral observations obtained at Yellow River Station (magnetic latitude 76.24°N) at Ny-Alesund, Svalbard, we performed the first extensive survey for the dayside diffuse auroras (DDAs) and acquired observational results as follows.(1) The DDAs can be classified into two broad categories, i.e., unstructured and structured DDAs. The unstructured DDAs are mainly distributed in morning and afternoon, but the structured DDAs predominantly occurred around the magnetic local noon (MLN). (2) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 75 publications
(112 reference statements)
5
89
1
Order By: Relevance
“…Are there specific solar wind conditions that lead to jets that trigger reconnection, so that it could be forecasted? Possible Connection Between Jets and Dayside 'Throat Aurora' Recently, Han et al (2015Han et al ( , 2016Han et al ( , 2017 found that dayside diffuse auroras observed near magnetic local noon often show discrete north-south aligned arcs extending from low latitudes towards the equatoward edge of the main auroral oval (Fig. 42).…”
Section: Nature Of Jet Boundariesmentioning
confidence: 99%
“…Are there specific solar wind conditions that lead to jets that trigger reconnection, so that it could be forecasted? Possible Connection Between Jets and Dayside 'Throat Aurora' Recently, Han et al (2015Han et al ( , 2016Han et al ( , 2017 found that dayside diffuse auroras observed near magnetic local noon often show discrete north-south aligned arcs extending from low latitudes towards the equatoward edge of the main auroral oval (Fig. 42).…”
Section: Nature Of Jet Boundariesmentioning
confidence: 99%
“…Recently, a particular auroral form, manifested as a localized equatorward extension of the equatorward edge of the east‐west aligned persistent midday auroral oval, has been observed near the dayside convection throat region. This auroral form has been named “throat aurora” (Han et al, ). Coordinated low‐altitude satellite observations show that throat auroras are caused by magnetosheath‐like particles and are suggested to be associated with localized magnetopause deformations (Han et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…throat region. This auroral form has been named "throat aurora" (Han et al, 2015). Coordinated low-altitude satellite observations show that throat auroras are caused by magnetosheath-like particles and are suggested to be associated with localized magnetopause deformations (Han et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Study of the morphology and evolution of aurora is not only helpful for revealing the solar wind-magnetosphere-ionosphere coupling processes and their internal mechanisms but also provides important physical principles for space weather forecasting (Nishimura et al, 2010;Hu et al, 2009Hu et al, , 2010Hu et al, , 2012Hu et al, , 2013Hu et al, , 2017aHan et al, 2015Han et al, , 2016Han et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%